REPRODUCTIVE BIOLOGY OF RASBORA PHILIPPINA AT LAKE WOOD FOR BASIS MANAGEMENT - Genovia, Jerson A.; Barquilla, Manuel B.; Baludo, Marjohn Y. (Journal of Environmental Science and Sustainable Development, 2023)
Rasbora philippina is an endemic species in Mindanao Island, Philippines. Its reproductive biology remains unstudied despite its economic importance to the local inhabitants of the lake, the Subanen tribe. Due to its marketability, Rasbora faces local threats. Thus, the formulation of fishery management and conservation recommendations is highly recommended. A research-made survey was used to interview fishermen in the lake, and fish samples were collected using a seine net with a catch per unit effort of three or four from March to May 2019. Water samples were collected using a Niskin water sampler at 1 m and 15 m depths during the same period. The reproductive biology of the fish was determined using the following data: sex ratio, maturity stages, age and population structure, fecundity, gonadosomatic index, and length-weight relationship. During the study period, the water quality was highly variable, still in good condition, and could still support the population of R. philippina. There were 31 male and 403 female individuals with a mean fecundity of 2,645.67, suggesting that there were more females than males, compensating for the low fecundity of R. philippina. The species does not spawn continuously, as mature individuals were absent throughout the study. However, this species is continuously recruited due to the presence of juveniles in the entire sampling period. Peak spawning was in early and mid-March and mid-April. Based on the results, we suggest that the open fishing season should be in early April, late April, and the third week of March, while the closed season for fishing would be in early March and late March. Thus, the management and conservation of R. philippina should always include careful consideration of the facts presented in this present work.